Pendapatan Ekonomi Ibu Menyusui Berpengaruh Tehadap Kwalitas Komponen Makronutrien ASI - Nina Hidayatunnikmah (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2019)
ABSTRACT Indonesian socioeconomic experienced a prolonged crisis, which causes families unable to got decent, good, and nutritious food due to rising prices soaring or decreasing the amount of individual income (Arisman, 2004). Individual income is one of the socio-economic factors that can affected family food security. Low economic income indicated poor family food security, where food consumption patterns of breastfeeding mothers will be disrupted and have an impact on the amount and composition of nutritional milk. Breast milk has a good nutritional component for babies. The macronutrient component of breast milk influenced the prosess of growth and development of infants. This research was analytic observational research type cross sectional study design through observations on all breastfeeding mothers with children aged 1-2 months in the work area of Wonoksumo health center to determine the effect of economic income of breastfeeding mothers on the quality of the macronutrient component of breast milk. Breastfeeding of macronutrient component of ASI research using MIRIS human milk analyzer tool and income variable were measured using questionnaires. The data analysis used Categorical Regression. The result of this research shows that there were influence of economic income on protein and fat component of breast milk (P=0,02, P=0,000). The conclusion of this study showed that economic income of nursing mothers can affected the components of protein and fat in breast milk. Keywords: Income, Brestfeeding mothers, Breast milk component